PREPARATION AND PROVIDING FINANCIAL INFORMATION, CORRECTION OF MISTAKES IN REPORTING COMPLIANCE WITH THE PRINCIPLES OF IFRS - Zinaida P. Arharova (Статистика и экономика, 2016)
In this article the main questions of preparation of ﬁnancial information (IFRS 1) areconsidered. In this text the main requirements of users to accounting (ﬁnancial information) are expressed. The principlesof preparation and drawing up ﬁnancial statements aren’t standards, it is possibleto divide them in three main groups. In article each of these groups are considered.